2019
DOI: 10.1161/strokeaha.119.025411
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Clinical Outcomes of Large Vessel Occlusion Before Mechanical Thrombectomy Using Machine Learning

Abstract: Background and Purpose— The clinical course of acute ischemic stroke with large vessel occlusion (LVO) is a multifactorial process with various prognostic factors. We aimed to model this process with machine learning and predict the long-term clinical outcome of LVO before endovascular treatment and to compare our method with previously developed pretreatment scoring methods. Methods— The derivation cohort included 387 LVO patients, and the external val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
113
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(120 citation statements)
references
References 30 publications
5
113
0
2
Order By: Relevance
“…Recent research has shown that it is possible to predict the clinical outcome of patients undergoing MTB in the context of AIS using ML models based on clinical variables, 22 and this may provide better decision support to perform MTB in some patients. In a complementary manner, our study showed that it is possible to guide the endovascular procedure based on imaging biomarkers contained in the pretherapeutic imaging of the clot.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has shown that it is possible to predict the clinical outcome of patients undergoing MTB in the context of AIS using ML models based on clinical variables, 22 and this may provide better decision support to perform MTB in some patients. In a complementary manner, our study showed that it is possible to guide the endovascular procedure based on imaging biomarkers contained in the pretherapeutic imaging of the clot.…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, clinical variables were not used in this study. Previous studies demonstrated the effectiveness of clinical variables in the prediction of infarct growth [34] and clinical outcome [35], while our study was solely based on image features. The inclusion of clinical variables may help improve the outcome prediction.…”
Section: Discussionmentioning
confidence: 99%
“…According to Wolpert's "No Free Lunch Theorem, " no one technique will be most accurate in every case, and so comparisons of techniques in different research areas and datasets may yield different results (15). Therefore, we used 5 ML algorithms: LR, SVM, RFC, XGBoost, and DNN because they are widely and successfully used for clinical data (16)(17)(18)(19)(20).…”
Section: Model Developmentmentioning
confidence: 99%